2020
DOI: 10.1098/rsos.191270
|View full text |Cite
|
Sign up to set email alerts
|

The seepage flow characteristics of hydrophobically associated polymers with different aggregation behaviours in porous media

Abstract: The polymer solution for oil displacement is subjected to strong shear action in practical application, and this action will affect its percolation characteristics in porous media. The effects of mechanical shearing on the solution properties and seepage characteristics of modified hydrophobically associated polymers and dendrimers with two different aggregation behaviours were studied. The results showed that mechanical shearing did not affect hydrophobic microzones. Polymers can re-associate to restore part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…DHAP has a relative molecular weight of 6 million and a hydrophobic group content of 0.6 mol %. The specific synthesis steps have been reported in previous literature [ 11 , 25 , 26 ], and its molecular formula is shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DHAP has a relative molecular weight of 6 million and a hydrophobic group content of 0.6 mol %. The specific synthesis steps have been reported in previous literature [ 11 , 25 , 26 ], and its molecular formula is shown in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the most widely used polymer solutions for oil displacement in oilfields are partially hydrolyzed polyacrylamide (HPAM) and the hydrophobically associating polymer AP-P4 [ 21 , 22 , 23 , 24 ]. The use of dendrimer hydrophobically associating polymers (DHAPs) is one of the leading research methods to improve complex reservoir conditions [ 25 , 26 ]. Among them, the adsorption mechanism and influencing factors of HPAM are more prominent.…”
Section: Introductionmentioning
confidence: 99%
“…The polymers used for the experiment were: (1) partially hydrolyzed polyacrylamide (HPAM), with a relative molecular weight of 20 million, hydrolysis degree of 26.3%, and solid content of 88.9% (Industrial Products), 32 the molecular formula of which is shown in Figure 1, Daqing oilfield production; (2) hydrophobically modified partially hydrolyzed polyacrylamide (HMPAM), with a relative molecular weight of 12 million, a degree of hydrolysis of 20%, and a hydrophobic group content of 1.2 mol%, the molecular formula of which is shown in Figure 2, self synthesis 33 ; (3) dendritic hydrophobically associating polymer (DHAP), with a relative molecular weight of 6 million, hydrolysis degree of 25%, hydrophobic group content of 0.6 mol%, and branching degree of 1, the molecular formula of which is shown in Figure 3. The specific steps of synthesis and the results of NMR analysis of the products are shown in refs 33 and 34 (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the synthesis of polymer flooding agents mainly focuses on improving the performance of the solution by chemically modifying the molecular structure of the polymer and introducing functional groups to produce functional polymers [6][7][8]. More recent studies focus on the synthesis and characterization of the hydrophobic groups linked to polymers of dendritic structures [9]. Based on the synthesis of dendritic polymers, a large number of researchers have conducted comparative performance studies, and the results are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%